Polymorphisms in the promotor region of the CRBN gene as a predictive factor for peripheral neuropathy in the course of thalidomide‐based chemotherapy in multiple myeloma patients. (22nd May 2019) - Mlak, Radosław; Szudy‐Szczyrek, Aneta; Mazurek, Marcin; Szczyrek, Michał; Homa‐Mlak, Iwona; Mielnik, Michał; Chocholska, Sylwia; Jankowska‐Łęcka, Olga; Małecka‐Massalska, Teresa; Hus, Marek
Summary: Thalidomide is commonly used in treatment of multiple myeloma (MM). This study aimed to analyse the influence of clinical and molecular factors ‐ single nucleotide polymorphisms (SNPs) of the CRBN gene: rs6768972 and rs1672753, on the risk of adverse effects (AEs) of thalidomide‐based chemotherapy in patients with MM. The study group included 82 patients receiving CTD (thalidomide, cyclophosphamide, dexamethasone) as first line treatment. The intensity of haematological and non‐haematological AEs was assessed according to the Common Terminology Criteria for Adverse Events v4.03. Multivariate analysis showed that patients with the CRBN CC genotype (rs1672753) had more than a 14‐fold higher risk of peripheral polyneuropathy compared to patients with other variants of the investigated SNP [odds ratio (OR) = 14·29]. Carriers of this genotype were burdened with significantly (about 17‐fold) higher risk of diarrhoea during treatment (OR = 16·67). The presence of CRBN AA (rs6768972) or TT (rs1672753) genotypes was associated with about 333‐fold and 250‐fold lower risk of constipation in the course of therapy (OR = 0·003; OR = 0·004, respectively). Selected CRBN SNPs may be useful in assessing the probability of AEs in the form of peripheral polyneuropathy and gastrointestinal motility disorders associated with the use of thalidomide in patients with MM.